Poverty and the Linkage to Criminal Enhancement and Human Trafficking in Cambodia - Dwi Ardiyanti (Indonesian Journal of International Relations, 2017)
Poverty relates to other problems in the worlds. Cambodia as one of the developing counrtries faced human trafficking problems caused by poverty post civil war. It should be solved first before it compete with other countries in globalization era. The effort of government is important and should be conducted with the cooperation among all agents.